Recent Advances in Multidimensional (1D, 2D, and 3D) Composite Sensors Derived from MXene: Synthesis, Structure, Application, and Perspective. Issue 7 (31st May 2021) - Wang, Lin; Zhang, Meiyun; Yang, Bin; Tan, Jiaojun; Ding, Xueyao; Li, Weiwei
Abstract: With the advent of the era of intelligent manufacturing, sensors, with various detection objects, have set off a wave of enthusiasm and reached new heights in medical treatment, intelligent industry, daily life, and so on. MXene, as an emerging family of 2D transition metal carbides/nitrides, possesses impressive electrical conductivity, outstanding structural controllability, and satisfying universality with other substrates. Consequently, MXene‐based sensors with various functions show a booming growth based on great research potential of MXene. To promote the orderly and efficient development of MXene application in sensors, and further accelerate market‐scale application of ideal sensors, in this review, a full range research effort on current MXene‐based sensors is summarized. Starting with various synthesis methods of the raw material MXene, a comprehensive summary work along with 1D, 2D, or 3D MXene‐based sensors on most recent works is put forward, including the preparation method, characteristic structure, and potential sensing application of each type of MXene‐based composite sensors. Ultimately, insights of the opportunities and challenges on the strength of the current reported MXene‐based sensor are given. Abstract : A comprehensive summary work along with 1D, 2D, or 3D MXene‐based sensors on most recent works is put forward, including the preparation method, characteristic structure, and potential sensing application of each type of MXene‐based composite sensors. Additionally, the possible challenges and outlook of the future development of MXene‐based sensors are highlighted in the end.